Discourse analysis - Johnstone, Barbara (Malden, MA : Blackwell, 2008)
"This popular introductory textbook is now available in a revised and updated second edition. Assuming no previous background in linguistics, it encourages students to think about discourse analysis as an open-ended set of techniques, carefully balancing the coverage of topics with extensive practical examples." "Johnstone considers a variety of approaches to the subject, including critical discourse analysis, conversation analysis, interactional and variationist sociolinguistics, ethnography, corpus linguistics, and other qualitative and quantitative methods. Detailed descriptions of the results of discourse analysts' work are also featured. The second edition retains and expands the useful student features, including discussion questions, exercises, and ideas for small research projects. This combination of breadth of coverage, practical examples, and student-friendly features makes Discourse Analysis the ideal textbook for students taking their first course in linguistic approaches to discourse."--BOOK JACKET
1. Introduction -- 2. Discourse and world -- 3. Discourse structure: parts and sequences -- 4. Participants in discourse: relationships, roles, identities -- 5. Prior texts, prior discourses -- 6. Discourse and medium -- 7. Intention and interpretation -- 8. Some general themes
Includes bibliographical references (pages [277]-301) and index
Keywords: Discourse analysis